Risk factors associated with cancer in the elderly. Medical Office 20 - Hernández Baño, Adnaloy; Díaz Pita, Gicela; Sparis Tejido, Mario Manuel; Núñez Díaz, Brenda de la Caridad; Pando Camejo, Dianelys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Cancer can be considered as a disease of the Older Adult since more than 65% of all malignant Neoplasms occur in this group, the risk of cancer usually increases with age due to a longer period of exposure to numerous carcinogenic elements. Objective: to characterize the risk factors associated with cancer in older adults belonging to the medical office 20 of the Pedro Borrás Astorga polyclinic, in the period September 2018 to May 2019. Method: an observational, analytical and cross-sectional study was conducted, the universe was constituted by 321 older adults, a sample of 90 older adults was selected, by non-probabilistic intentional sampling, theoretical, empirical and descriptive statistical methods were used. Results: there was a predominance of the age group 65-69 years, 64% of the female sex, 50% were normal weight, 40% were sedentary, 45% had up to 3 associated risk factors such as bad eating habits, smoking and alcoholism; family and personal pathological antecedents were arterial hypertension. Conclusions: several risk factors predominate in the elderly; this favors the appearance of a type of cancer. Actions aimed at the prevention and modification of risk factors are required to reduce the incidence of cancer and achieve a satisfactory longevity.